Buccal alveolar bone changes following rapid maxillary expansion and fixed appliance therapy - Sperl, Adam (Angle Orthod, 2020)
OBJECTIVES: To assess factors that may be associated with buccal bone changes adjacent to maxillary first molars after rapid maxillary expansion (RME) and fixed appliance therapy. MATERIALS AND METHODS: Pretreatment (T1) and posttreatment (T2) cone-beam computed tomography scans were obtained from 45 patients treated with RME and preadjusted edgewise appliances. Buccal alveolar bone thickness was measured adjacent to the mesiobuccal root of the maxillary first molar 4 mm, 6 mm, and 8 mm apical to the cementoenamel junction, and anatomic defects were recorded. Paired and unpaired t-tests were used to compare alveolar bone thickness at T1 and T2 and to determine whether teeth with posttreatment anatomic defects had thinner initial bone. Correlation analyses were used to examine relationships between buccal alveolar bone thickness changes and amount of expansion, initial bone thickness, age at T1, postexpansion retention time, and treatment time. RESULTS: There was a statistically significant reduction in buccal alveolar bone thickness from T1 to T2. Approximately half (47.7%) of the teeth developed anatomic defects from T1 to T2. These teeth had significantly thinner buccal bone at T1. Reduction in alveolar bone thickness was correlated with only one tested variable: initial bone thickness. CONCLUSIONS: RME and fixed-appliance therapy can be associated with significant reduction in buccal alveolar bone thickness and an increase in anatomic defects adjacent to the expander anchor teeth. Anchor teeth with greater initial buccal bone thickness have less reduction in buccal bone thickness and are less likely to develop posttreatment anatomic defects of buccal bone.